Selection of temporary landfill using fuzzy multiple attribute - Muslihudin M.; Purnama R.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
It is realized that the selection of temporary landfill, bahasa: Tempat Pembuangan Sampah (TPS) is very complicated in view of many factors that need to be considered. Therefore it is needed the criteria that can be used to determine the location of landfill that is feasible and meets the requirements. The requirements are stated in the Indonesian National Standard (SNI) 03-3241-1994 about procedures for selecting landfill sites. In this study, it was arranged based on regional stages, where the stages in resulting map contain the area within the planning area divided into several feasibility zones. By using the method of Simple Additive Weighting it makes easy to perform data analysis to results very good, good and bad decisions for selected location. BEIESP.